The prevalence and distribution of comorbidities involved in elderly patients in a health unit of the municipality of Cascavel-PR (Research, Society and Development, 2023)
The present study aimed to characterize the distribution of the most prevalent comorbidities and to analyze the association of such comorbidities with sociodemographic characteristics in the geriatric population at the outpatient level in a Basic Health Unit in the municipality of Cascavel-PR in 2022 in order to obtain knowledge about their distributions in the region, as well as the modifiable factors that can be intervened by health professionals and managers. This cross-sectional study was carried out based on the analysis of medical records of elderly patients undergoing outpatient follow-up, dated January 2022. During the study period, the medical records of 111 patients who met the inclusion criteria were analyzed. Among the evaluated, 76 (68.5%) were female and 35 (31.5%) were male. Regarding the age group, 68 (61.3%) were 60 to 69 years old, 32 (28.8%) had 70 to 79 years and 11 (9.9%) were 80 years or older. Among the main comorbidities identified in the period studied, arterial hypertension predots, representing 60.4% of the patients analyzed. Followed by dyslipidemia (48.6%), obesity (24.3%), Type 2 Diabetes Mellitus (19.8%) and Major Depressive Disorder (18%). In this sense, it is concluded that there is a need to promote research on the aforementioned diseases, given their high prevalence in the geriatric population, thus improving public policies aimed at these priority groups.